PENGARUH LATAR BELAKANG PENDIDIKAN GURU SMP/MTs TERHADAP HASIL UN BAHASA INGGRIS 2019 - Safari Safari (Akademika : Jurnal Teknologi Pendidikan, 2019)
The main purpose of this study is to answer the following question. Is there an influence on the educational background of SMP / MTs teachers on the results of the 2019 English National Examination. The population of this study is the SMP / MTs teachers who teach subjects that are UN-2019. The data in this study are in the form of test scores and teacher answers to the questionnaire in 34 provinces throughout Indonesia. The questionnaire was completed voluntarily on the last day of the UN, so the number of respondents who filled out the questionnaire was 97052SMP / MTs teachers. The number of respondents is a sample in this study. Based on the results of the analysis of descriptive and variants of one path obtained the following results. The educational backgrounds of junior high / middle school teachers in the highest to lowest order are: (1) S-1, 88.4%; (2) S-2, 6.3%; (3) SMA / D1, 3.7%; (4) D-3, 1.6%; (5) S-3, 0.1%. Whereas the certified teachers were only half, namely 53.2%.The effect of the influence of teacher education background on the 2019 English National Examination results is proven. This means that there is a significant influence (P <0,000) of teacher education background on the results of the 2019 English Language Examination (Sig. 0,000). The conclusion is that there is an influence of teacher education background on the 2019 English National Examination results